2013
DOI: 10.1007/s10557-013-6504-7
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Metformin Treatment is Associated with Reduced Myocardial Infarct Size in Diabetic Patients with ST-segment Elevation Myocardial Infarction

Abstract: Chronic metformin treatment is associated with reduced MI size compared to non-metformin based strategies in diabetic patients presenting with STEMI. Metformin might have additional beneficial effects beyond glucose lowering efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 36 publications
5
49
0
Order By: Relevance
“…Recent animal studies [12,14,21] have demonstrated a cardioprotective effect of metformin in non-diabetic rats subjected to coronary ligation. An observational human study suggested reduction in infarct size in patients with diabetes on metformin therapy undergoing PCI for STEMI [22]. All this information formed the basis of a recently reported study designed to look at the LVEF in non-diabetic patients with STEMI undergoing PCI treated with metformin [16].…”
Section: Discussionmentioning
confidence: 99%
“…Recent animal studies [12,14,21] have demonstrated a cardioprotective effect of metformin in non-diabetic rats subjected to coronary ligation. An observational human study suggested reduction in infarct size in patients with diabetes on metformin therapy undergoing PCI for STEMI [22]. All this information formed the basis of a recently reported study designed to look at the LVEF in non-diabetic patients with STEMI undergoing PCI treated with metformin [16].…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical study reported that metformin did not improve LVEF in ST-elevated MI (STEMI) nondiabetic patients (Lexis et al 2014a). However, metformin improved clinical outcomes in metabolic syndrome patients undergoing percutaneous coronary intervention ) and reduced MI size in diabetic patients with STEMI (Lexis et al 2014b). Furthermore, metformin has been shown to improve cardiac function in normal rats with chronic MI (Soraya et al 2012(Soraya et al , 2014.…”
Section: Figurementioning
confidence: 98%
“…In humans, a recent retrospective cohort study sought to investigate the association between metformin use and MI size in patients presenting with an acute MI 10. The researchers divided patients with diabetes into metformin versus nonmetformin groups and estimated MI size using peak values of serum creatine kinase, CKMB, and troponin T 10.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2013 retrospective analysis, Zhao et al found that chronic pretreatment with metformin was associated with the reduction of the no‐reflow phenomenon in patients with diabetes mellitus after primary angioplasty for acute MI 9. In a 2014 retrospective cohort study, Lexis et al sought to investigate the association between metformin use and MI size in patients presenting with an acute MI 10. The researchers found that the use of metformin treatment was an independent predictor of smaller MI size 10.…”
Section: Introductionmentioning
confidence: 99%